Building Digital Libraries : A How-To-Do-It Manual for Librarians - Banerjee, Kyle; Reese Jr., Terry (Chicago, Illinois : ALA Neal-Schuman, an imprint of the American Library Association, 2019)
Whether you're embarking on the challenge of building a digital collection from scratch, or simply need to understand the conceptual and technical challenges of constructing a digital library, this top-to-bottom resource is the ideal guidebook to keep at your side, especially in this thoroughly updated and reworked edition.
Includes index
Keywords: Digital libraries